Investigating Relationships between Reproduction, Immune Defenses, and Cortisol in Dall Sheep - Downs, Cynthia J.; Boan, Brianne V.; Lohuis, Thomas D.; Stewart, Kelley M. (Frontiers in Immunology, 2018)
Life-history theory is fundamental to understanding how animals allocate resources among survival, development, and reproduction, and among traits within these categories. Immediate trade-offs occur within a short span of time and therefore are more easily detected. Trade-offs, however, can also manifest across stages of the life cycle, a phenomenon known as carry-over effects. We investigated trade-offs on both time scales in two populations of Dall sheep (Ovis dalli dalli) in Southcentral Alaska. Specifically, we (i) tested for glucocorticoid-mediated carry-over effects from the breeding season on reproductive success and immune defenses during parturition and (ii) tested for trade-offs between immune defenses and reproduction within a season. We observed no relationship between cortisol during mating and pregnancy success; however, we found marginal support for a negative relationship between maternal cortisol and neonate birth weights. Low birth weights, resulting from high maternal cortisol, may result in low survival or low fecundity for the neonate later in life, which could result in overall population decline. We observed a negative relationship between pregnancy and bacterial killing ability, although we observed no relationship between pregnancy and haptoglobin. Study site affected bactericidal capacity and the inflammatory response, indicating the influence of external factors on immune responses, although we could not test hypotheses about the cause of those differences. This study helps advance our understanding of the plasticity and complexity of the immune system and provides insights into the how individual differences in physiology may mediate differences in fitness.